2006
DOI: 10.1111/j.1365-2885.2006.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Fumagillin, a new P‐glycoprotein‐interfering agent able to modulate moxidectin efflux in rat hepatocytes1

Abstract: We have tested the ability of two compounds licensed in veterinary medicine: fumagillin and diminazene diaceturate to increase intracellular moxidectin quantity in rat hepatocytes. These compounds significantly increased the quantity of 14C-moxidectin (expressed as area under the time curve concentrations) in cultured rat hepatocytes by 44% and 65% for diminazene and fumagillin treatments respectively. In addition, we have tested these drugs for their interference with P-glycoprotein (P-gp) function in porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…More recently, the use of ketoconazole in dogs [118] or sheep [119] and itraconazole in sheep [120] or rat [82], in combination with ivermectin, doubled the area under the plasma concentration-time curve compared with ivermectin alone. Recently, another compound fumagillin was also shown to increase the ML bioavailability likely through inhibition of P-gp [121]. Lowering the therapeutic dose of ivermectin could also be considered when it is co-administered with such MDR transport inhibitors.…”
Section: Helping the Mls To Work Bettermentioning
confidence: 97%
“…More recently, the use of ketoconazole in dogs [118] or sheep [119] and itraconazole in sheep [120] or rat [82], in combination with ivermectin, doubled the area under the plasma concentration-time curve compared with ivermectin alone. Recently, another compound fumagillin was also shown to increase the ML bioavailability likely through inhibition of P-gp [121]. Lowering the therapeutic dose of ivermectin could also be considered when it is co-administered with such MDR transport inhibitors.…”
Section: Helping the Mls To Work Bettermentioning
confidence: 97%
“…The interaction of MXD with the ABC transporters was demonstrated in cultured rat hepatocytes. Ketoconazole, quercetin and fumagillin increased the quantity of 14C-moxidectin in hepatocytes [80,81]. It has been recently shown that affinity by P-gp may differ among different ML molecules [23].…”
Section: In Vitro and Ex Vivo Experimental Ap-proachesmentioning
confidence: 98%
“…These experiments include in vitro analyses of the effects of flavonoids on the intracellular accumulation of P-gp substrates using P-gp-overexpressing cells and a variety of clinical and animal model studies, especially involving P-gp knockout animals [37]. For example, concomitant administration of quercetin increased moxidectin oral bioavailability in lambs [72]; oral bioavailability of quinine was increased by naringin [73]; cyclosporine by baicalein and its aglycone [74]; and paclitaxel by flavones in rats [75]. Similarly, quercetin increased the oral bioavailability of paclitaxel and tamoxifen in rats [76,77] and digoxin in pigs, which results in high toxicity [78].…”
Section: Flavonoids As P-gp and Cyp3a Modulatorsmentioning
confidence: 99%